Social engineering : the art of human hacking - Hadnagy, Christopher (Indianapolis, IN : Wiley, 2011)
Examines what social engineering is, the methods used by hackers to gather information, and ways to prevent social engineering threats.
A look into the world of social engineering -- Information gathering -- Elicitation -- Pretexting: how to become anyone -- Mind tricks: psychological principles used in social engineering -- Influence: the power of persuasion -- The tools of the social engineer -- Case studies: dissecting the social engineer -- Prevention and mitigation.
Includes index.
Keywords: Social engineering; Hackers; Computer security; Human-computer interaction; Social engineering; Computer hackers; Computer security